Exercise equilibrium radionuclide angiography predicts long-term cardiac prognosis in patients with abdominal aortic aneurysm being considered for surgery. - Kelion, A; Banning, A; Gardner, M; Ormerod, O (2000)
BACKGROUND: Patients with an abdominal aortic aneurysm (AAA) have a high prevalence of coronary disease and are at risk for cardiac events. This may offset the prognostic benefit of surgical repair. We investigated whether preoperative exercise equilibrium radionuclide angiography (ERNA) could be used to identify patients at high risk for cardiac events after successful AAA repair. METHODS: Between 1990 and 1995, 173 patients with an AAA were referred for supine bicycle exercise ERNA preoperatively. Follow-up information was obtained from a questionnaire sent to each patient's family physician. Cardiac events were defined as cardiac death or nonfatal myocardial infarction. RESULTS: A total of 139 patients were able to exercise and did not die or suffer myocardial infarction perioperatively. The median follow-up period was 3.8 years. Diabetes mellitus, an exercise ejection fraction (EF) below 0.50, and a fall in EF with exercise were univariable predictors of cardiac risk during the follow-up period (P < .05). On multivariable analysis, diabetes mellitus (risk ratio [RR], 6.9; 95% CI 1.5 to 32.0) and an EF fall (RR, 4.1; 95% CI 1.5 to 11.4) emerged as the most important predictors. CONCLUSIONS: Exercise ERNA predicts long-term cardiac events in patients being considered for elective AAA repair. Such predictive information may influence the decision to operate, for example, on small unthreatening aneurysms, or lead to invasive cardiological management to minimize risk.